Putting Web 2.0 into public administration: some answers - Zambrano-Silva, Salvador (Anuario ThinkEPI, 2009)
The previous note present some questions that emerged while considering whether to include services of the social web in the web page of the public organisation where the author works. Here some reflections, commentaries, projects or proposals are offered that can be possible answers to these questions.